DIFFERENCES IN LABOR PAIN INTENSITY AFTER THE PROVISION OF MUSIC THERAPY TO PRIMIGRAVIDA MOTHERS INPARTU KALA - Ika Wijayanti; Sri Wahyuni; Emaretha Mikaningtyas; Tina Endah Pratiwi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Introduction: Most laboring women are experiencing physical pain that is also accompanied by emotional fear. The latter may cause a slower development of labor, which prompt these mothers to opt for cesarean section. About 60% of primiparous and 40% of multiparous women had experienced extremely severe labor pains during the acute phase, and up to 40% of laboring women were not satisfied with the pain relief effect after taking analgesic drugs. Music therapy is one of the non-pharmacological pain reliever methods that helps one to relax and manage the mind and body’s perception against the agony. Aims: The objective of this study is to know the difference of pain intensity before and after the provision of music therapy to the primiparous mother in first stage of labor. Methods: Twenty primiparous who were expected to have a normal, spontaneous delivery were the experimental group (n = 20). A self-report visual analog scale (VAS) for pain intensity was used to measure the labor pain. The expecting mothers listened to the classical Mozart’s and Beethoven’s compositions for 10 minutes and then asked to scale the intensity of the pain that they felt before and after listening to the music. Data analysis was done by using univariate analysis and different t-test. Results: The results showed there was a significant difference of the intensity of pain before and after the provision of music therapy to the primiparous mother in the first stage of labor. Conclusion: This study provides evidence that the use of music therapy can reduce labor pain. Therefore, management of maternal care should include music therapy in assisting childbirth.